Knowledge Production in the Knowledge Economy: Higher Education Institutions and the Application of Innovations in ICT for Capacity Development in Africa - Evoh, CJ; Mugimu, Christopher; Chavula, Hopestone (2014)
[FRGMNT] … 16.7 101.6 34.1 6 6.1 0 20 40 60 80 100 120 Pre-primary Primary secondary TVET Tertiary Fig. 1. Education Access in Sub-Saharan Africa (% GER), 2011. Sources: Nsapato, Limbani (2012). Knowledge Production in the Knowledge Economy 295 Page 12 … [...]… RESEARCH METHODOLOGY Data for the study was gathered through qualitative research method, and theory-driven multiple case study approach was adopted (Yin, 2004) to examine the higher education system in Kenya and Uganda (East Africa) … [...]… Data for the study was gathered through qualitative research method, and theory-driven multiple case study approach was adopted (Yin, 2004) to examine the higher education system in Kenya and Uganda (East Africa) … 120 Pre-primary Primary secondary TVET Tertiary Fig …
Keywords: -FullBiblioUHMLgen; -RRQ:LOW; A:Africa; A:East Africa; A:Sub-Saharan Africa; C:Kenya; CA:AandC; CL:de; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:access; P:economy; P:measurement; P:production; Q:ICT; Q:higher education; R:case study; R:qualitative; R:research method; T:TVET; _C:Uganda UGA; publicImportV1; ⛔ No DOI found